The effect of cobalt bullets supplement in sheep (Revista da Faculdade de Medicina Veterinária, Universidade de São Paulo, 1966)
The effect of cobalt bullets — 90% cobalt oxide — was studied in sheeps grazing on deficient areas of that element. The treatment was carried on with half part of the animals, equaled by age, body weight and degree of blood, chiefly Corriedale. The results obtained, during twelve months, based on the rate of growth, the hemoglobin level and the score of red corpuscles, showed that cobalt bullets did not prove to be of any advantage to tested animals in no one of the considered aspects.